Isolation, Identification and Phenotypic Analysis of the Oral Bacterial Species from Supragingival Dental Plaque and Their Association with Different Factors - Kashif, Mehwash; Kazmi, Mahmooda; Tanwir, Farzeen; Akbar, Shazia; Mujtaba, Fatima; Gul, Somia (Bangladesh Journal of Medical Science, 2025)
Objective The objective of this study was to isolate and characterize oral aerobic, facultative anaerobic, and microaerophilic bacterial species from supragingival plaque and to evaluate the association of different demographic, phenotypic, and biochemical characteristics with the identified organisms. Material and Methods This prospective cross-sectional study enrolled 101 bacterial isolates sampled from the supragingival plaque, using sterile swab. Oral bacterial species were identified through biochemical and phenotypic analysis using standardized methods. The inclusion criteria were participants of Karachi, residents of both genders, being at least eighteen years old, having a Loe and Silness plaque index. Participants with severe systemic illnesses, such as immunodeficiency disorders, on chemotherapeutic drugs, antibiotic therapy twelve weeks before sampling persistent systemic infections, or known communicable diseases, were excluded. All details were recorded on proforma and data was analyzed by using SPSS version 22.0. p-value of < 0.05 was considered significant. Results and Discussion Multiple bacterial Species were identified, with Gram-positive species predominating. Statistically significant variables included gender, age, occupation, hemolysis on blood agar, bile esculin hydrolysis, catalase, oxidase, ONPG, CIT, MALO, ODC, UREA, VP, GEL, nitrate, sucrose, mannitol, melibiose, and raffinose. It was found that considerable variation in the oral bacterial species exists influenced by multiple factors. Conclusion It has been concluded that multiple and variable Gram-positive and negative bacterial species have been isolated from supragingival dental plaque of local isolates. The demographic, phenotypic, and biochemical characteristics demonstrated statistically significant associations with the identified organisms. BJMS, Vol. 24 No. 04 October’25 Page : 1153-1166